Regeneracija skeletne mišičnine - mehanizmi, satelitske celice in dejavniki vpliva - Marš, Tomaž (Medicinski razgledi, 2011)
Skeletal muscle is the most abundant of the human body's tissues and it represents a substantial percentage of body mass. Its main function is contraction, which produces force for different types of movement. It also includes the contraction of skelet al muscles that enables locomotion, joint stabilization, posture maintenance and production of body heat. Overall, skeletal muscles play an important role in the body's long-term survival and are crucial for fast and efficient response to changes in the external environment, as well as for communication and command of the environment. The unique features of skeletal muscle morphology and function reflect its specialembryonic development. Skeletal muscles are constantly exposed to metabolic and mechanical injuries, particularly due to the high metabolic rateduring contractions. Efficient regeneration is a prerequisite for the maintenance of skeletal muscle mass and function, and it is essentially a recapitulation of embryonic myogenesis. In addition, muscle regeneration is a complex and multistep process which includes intricate direct and indirect cellular and trophic interactions.
Keywords: Mišica skeletna; Muscle, Skeletal; Anatomy And Histology; Rastne snovi; Regeneracija; Growth And Development; Injuries; skeletne mišice; Regeneration; mišice; Myofibrils; Growth Substances; Miofibrile